2014
DOI: 10.1186/1475-2875-13-359
|View full text |Cite
|
Sign up to set email alerts
|

Atovaquone and quinine anti-malarials inhibit ATP binding cassette transporter activity

Abstract: BackgroundTherapeutic blood plasma concentrations of anti-malarial drugs are essential for successful treatment. Pharmacokinetics of pharmaceutical compounds are dependent of adsorption, distribution, metabolism, and excretion. ATP binding cassette (ABC) transport proteins are particularly involved in drug deposition, as they are located at membranes of many uptake and excretory organs and at protective barriers, where they export endogenous and xenobiotic compounds, including pharmaceuticals. In this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Recently, increasing numbers of papers have focused on the mechanism of antimalarial drugs. Studies in 2014 showed that quinine significantly inhibited breast cancer resistance protein (BCRP) mediated and P‐gp‐mediated transport at concentrations within the clinically relevant prophylactic and therapeutic range, and inhibited adenosine triphosphate (ATP) binding cassette transporter activity . Quinidine and cinchonine, which have identical stereochemistry at carbons 8 and 9, exhibited stronger inhibition of human and Drosophila melanogaster serotonin receptor transporter (hSERT and dSERT) function than their enantiomers, quinine, and cinchonidine .…”
Section: Biological Activities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…Recently, increasing numbers of papers have focused on the mechanism of antimalarial drugs. Studies in 2014 showed that quinine significantly inhibited breast cancer resistance protein (BCRP) mediated and P‐gp‐mediated transport at concentrations within the clinically relevant prophylactic and therapeutic range, and inhibited adenosine triphosphate (ATP) binding cassette transporter activity . Quinidine and cinchonine, which have identical stereochemistry at carbons 8 and 9, exhibited stronger inhibition of human and Drosophila melanogaster serotonin receptor transporter (hSERT and dSERT) function than their enantiomers, quinine, and cinchonidine .…”
Section: Biological Activities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…For a wide variety of drugs, including several antimalarial compounds, drug transporters of the ATP-binding cassette (ABC), solute carrier (SLC), or solute carrier organic anion (SLCO) family are involved in transmembrane transfer (Konig et al, 2013). For example, mefloquine, quinine, and chloroquine are inhibitors or substrates of efflux pumps such as P-glycoprotein (P-gp/ABCB1) (Riffkin et al, 1996;Pham et al, 2000;Rijpma et al, 2014), multidrug-resistance protein 1 (MRP1, ABCC1) and multidrug-resistance protein 4 (MRP4, ABCC4) (Wu et al, 2005), and chloroquine and quinine have been identified as inhibitors and substrates of multidrug and toxin extrusion protein 1 (MATE1, SLC47A1) and organic cation transporters (OCTs) (Muller et al, 2011;Nies et al, 2012). In addition, there is evidence that quinine interacts with organic anion transporting polypeptides (OATPs), in particular OATP1A2, which has been shown to transport N-methyl-quinine (Kullak-Ublick et al, 2001;Shitara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Quinine concentrations were below the therapeutic range in 50% of the patients, however all were successfully treated for malaria. [20] As quinine is an inhibitor of P-gp,[21] an interaction with maraviroc, a P-gp substrate, cannot be excluded. Cobicistat would be expected to increase exposure to quinine via CYP3A4 inhibition.…”
Section: Resultsmentioning
confidence: 99%